First report of acanthocephalan Profilicollis altmani on a black-necked stilt Himantopus mexicanus - Jara, César (2019)
We record the presence of the acanthocephalan specie Profilicollis altmani in a black-necked stilt, Himantopus mexicanus, in the Northern coast of Peru. Profilicollis altmani had not been previously reported in H. mexicanus, this being the first report in a new host.